The Sneetches and other stories - Seuss, Dr. (New York : Random House, 1989)
Includes four humorous verse fantasies: The Sneetches, The Zax, Too Many Daves, and What was I Scared of?
Keywords: Fantasy; Stories in rhyme; Fantasy; Stories in rhyme